DISTRESS PSIKOLOGI PADA RESIKO KERENTANAN BUNUH DIRI - Husni, Husni; Asmawati, Widia Lestari (JURNAL MEDIA KESEHATAN, 2018)
Staying in prisons, making space for prisoners is restricted and isolated from society, confined and isolated situation can be a stressor that causes stress. The purpose of research is known relationship with psychological distress vulnerability adolescent suicidal inmates in prisons Class II A Bengkulu. Type descriptive analytic research with cross sectional approach. The sample in this study were all teenagers who inhabit prison inmates Class II A Bengkulu in November 2015, as many as 49 prisoners. Collecting data using questionnaires. The data analysis was conducted quantitative univariate, bivariate, and multivariate analysis. The result showed a small fraction of prisoners suffered psychological distress, most inmates aged ? 18 years, nearly all prisoners gender to male, mostly poorly educated prisoners, a fraction highly vulnerable inmates committed suicide. There is no significant relationship between psychological distress with the vulnerability of suicide on inmates in prisons Class II A Bengkulu. The need for counseling to the inmates of prisons in addressing various problems with doing something positive thereby prison occupants will be able to receive him at the moment, and look at everything positively.